2012
DOI: 10.4172/2157-7145.1000174
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study of Violent Asphyxial Death in Varanasi Region (India) a Killing Tool

Abstract: Asphyxial death is a common incident in forensic practices, and determination of the manner of death that may be accidental, suicidal, homicidal, or natural is of utmost significance. In such deaths, a detailed and meticulous autopsy plays a major role to solve the case while the scene investigation and collection of samples have their own significance. Domestic violence plays a great role in suicidal and homicidal violent asphyxia deaths. Various epidemiological and demographical parameters of the study are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
16
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 3 publications
12
16
0
2
Order By: Relevance
“…In our study, hanging was the commonest type of asphyxial death followed by drowning, which is consistent with the studies by various authors 1,6,7,9,10,11 but in one of the study 7 it was observed that the incidence of drowning being the commonest (59.40%) which could be due to the presence of water reserves in the region of the study. According to WHO report 2000 7 , Both China and India have particularly high drowning mortality rates and together contribute 43% of all drowning deaths worldwide.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In our study, hanging was the commonest type of asphyxial death followed by drowning, which is consistent with the studies by various authors 1,6,7,9,10,11 but in one of the study 7 it was observed that the incidence of drowning being the commonest (59.40%) which could be due to the presence of water reserves in the region of the study. According to WHO report 2000 7 , Both China and India have particularly high drowning mortality rates and together contribute 43% of all drowning deaths worldwide.…”
Section: Discussionsupporting
confidence: 81%
“…The asphyxial deaths was more in age group of 21-30yrs ( 38.89 %) which can be compared to other studies 3,5,7,10 , followed by the age group 31-40yrs ( 33.33%) which goes in favour of another study. 7 Males predominance was noticed in our study and male to female ratio is 3:1.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations